“STUDIES IN AFRICAN MUSIC” by REV. A. M. JONES. Oxford University Press, 1959. Vols. 1 and 2, pp. 295 and 238, 18 plates etc., 7 gns. (International Library of African Music, 1959)
pages: 84-89
Keywords: African Music